DAP lied about Pakatans unity, says don - News Straits, Times (New Straits Times Press, 2015)
KUALA LUMPUR: The opposition pact has not been truthful to the people.That is the opinion of Universiti Utara Malaysia political scientist, Dr Muhammad Fuad Othman, concerninga recent revelation by DAP adviser Lim Kit Siang on the brewing tension between PKR, DAP and Pas in their runup to the 13th General Election (GE13).